Post-Covid 19, Online consumer purchase behavior in Pakistan - Syed Muhammad Shaheer Uddin; Elleta Anneka Fernandes; Rida Zehra Merchant; Ushna Saulat; Muhammad Tabish (Institute of Business Management, 2023)
Since Covid-19, there has been a rise in e-commerce and online brands' influence on consumer buying behavior. It is crucial to investigate the factors that impact online consumer purchase behavior. Applying the theory of reasoned action (TRA), our study seeks to assess the extent to which customer satisfaction and perceived risks build trust and how trust, consumer engagement, and ease of purchase would act as reasons for consumers to engage in e-commerce in Pakistan. Using data gathered from 400 respondents via a questionnaire, we have demonstrated the precise relationship between these six constructs. Results indicate that customer satisfaction positively influences trust while perceived risks negatively affect it and that trust and consumer engagement positively and directly impact purchase behavior. Online retailers should improve these factors and modify the online environment to increase sales from their e-channels and improve customer retention